Effects of autologous platelet-rich plasma in promoting endometrial thickness on patients with thin endometrium following IVF - Pratama, Gita; Agustina, Elizabeth; Yanfaunnas, Atika Mahira; Maidarti, Mila; Harzif, Achmad Kemal; Muharam, R.; Wiweko, Budi (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS It was observed that autologous PRP substantially increased endometrial thickness in individuals experiencing infertility linked to a thin endometrium. The elevated clinical pregnancy rate emphasizes the favorable effectiveness of autologous PRP in addressing issues related to a thin endometrium in IVF programs.   ABSTRACT Objective: The objective of this research was to investigate the impact of autologous platelet-rich plasma (PRP) in enhancing endometrial thickness among individuals experiencing infertility associated with a thin endometrium. Materials and Methods: Nine individuals with a thin endometrium who participated in an in vitro fertilization (IVF) program were enrolled in the study. This study was carried out in Yasmin Clinic, Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Patients underwent a hormone replacement protocol involving the preparation of the endometrium with estradiol valerate. Treatment with PRP was initiated when the endometrial thickness was less than 7 mm. Autologous PRP was infused into the uterine cavity between the 10th and 12th days after administering estradiol valerate, and the assessment of endometrial thickness was conducted using ultrasound 48 hours later. A second administration of PRP was provided in cases where the endometrial thickness was below 7 mm. Frozen-thawed embryo transfer (FET) was performed if the endometrium reached adequate thickness (minimum 7 mm). Results: Seven of nine patients had adequate endometrial thickness followed by FET. Endometrial thickness was improved in 8 from 9 patients (88.8%). Five patients were improved at the first autologous PRP infusion (62.5%) and three patients (37.5%) at the second PRP infusion. The implantation rate was 33.3-100%, clinical pregnancy was 100%, and ongoing pregnancy rate was 83.3%. Conclusion: The use of autologous platelet-rich plasma (PRP) successfully stimulates endometrial development in individuals with a thin endometrium during frozen-thawed embryo transfer.